Efficacy of Daily Text Messaging to Support Adherence to HIV Pre-Exposure Prophylaxis (PrEP) among Stimulant-Using Men Who Have Sex with Men. (23rd February 2023) - Serrano, Vanessa B.; Moore, David J.; Morris, Sheldon; Tang, Bin; Liao, Antony; Hoenigl, Martin; Montoya, Jessica L.
Abstract: Background : Men who have sex with men (MSM) who use stimulants are at increased risk for HIV infection. Adherence to pre-exposure prophylaxis (PrEP) reduces the risk of HIV infection. We evaluated the efficacy of the individualized Texting for Adherence Building (iTAB) intervention for PrEP adherence compared to standard of care (SoC) among 119 MSM who use stimulants (cocaine, methamphetamine and/or other amphetamine) from the California Collaborative Treatment Group 595 randomized control trial. Method : Three ordered levels of PrEP adherence (non-adherence, adequate adherence, and near-perfect adherence) were compared between intervention arms across study visits (weeks 12 and 48) using ordinal logistic regressions. Results : The effect of intervention arm was not significant in the final model; however, there was a 38% decrease in odds (OR = 0.62, p =.023) of having near-perfect adherence (versus non-adherence or adequate adherence) at week 48 compared to week 12, indicating a significant effect of time. In a follow-up analysis examining week 48 only, logistic regression examining PrEP adherence showed that receiving iTAB (compared to SoC) trended toward higher odds of near-perfect adherence relative to adequate adherence (OR = 2.48, p =.061). Higher HIV knowledge resulted in higher odds (OR = 1.72, p =.020) of near-perfect adherence (versus non-adherence or adequate adherence). Conclusion : HIV knowledge may influence PrEP adherence, and most notably, the iTAB intervention may support near-perfect adherence relative to adequate adherence.